An assessment on the status and distribution of endemic and threatened birds of Siquijor Island, Philippines - Bucol, Abner A.; Bucol, Aladin B. (Silliman Journal, 2023)
An assessment on the status and distribution of endemic and threatened birds of Siquijor Island, Philippines: A progress report This paper presents the results of an on-going study on the avifauna of Siquijor Island utilizing point counts, transect walks, and MacKinnon Lists with ethnobiological surveys. The study covered the four major forest patches remain-ing on Siquijor and was visited during October — December 2007. A total of 44 species were recorded. Four of the five endemic subspecies were confirmed, namely: Streak-breasted Bulbul (Ixos siquilorensis siquilorensis), Yellow-bellied Whistler (Pachycephala phillppensis siquijorensis), Orange-bellied Flowerpecker (Dicaeum trigonostigma best') and Everett's White-eye (Zosterops everetti siquliarensis). The Philippine Hanging-Parrot (Loriculus siquijorensis) was not sighted at all and is presumed to be extinct. Of all the threatened species known to inhabit the island in the past, only the Streak-breasted Bulbul was sighted; it was found in all sites with relative indices of abundance of 1.0 in Bandilaan, Canghaling, and Liloan; and 0.92 in Salagdoong. Bandilaan Natural Park .harbors the highest num-ber of bird species (35) followed by Canghaling (33), Liloan (28) and Salagdoong (20). Habitat destruction due to firewood extraction and slash-and-burn farming as well as hunting were the observed threats to the island's avifauna and its unique biodiversity.